(untitled) (JOSAR (Journal of Students Academic Research), 2025)
Ability numeracy is element important things to do mastered the Merdeka curriculum for help student in data analysis and retrieval decision , while knowledge about product local introduce they are in diversity culture and improve love to product domestically . The research method used is research and development of the ADDIE model. Data collection in study This that is interviews , questionnaires , and tests . The methods used in study This that is using ( RnD ). With amount 14 students at SDN 2 Sukorejo , 14 students at SDN 2 Gandusari , 6 students at SDN 2 Ngrayung , and 20 students at SDN 1 Wonorejo . The results of the research conducted that is the validity of Domica media is already worthy used . Expert validator results Material , Media, Language got an average of 96% “very good” and expert practitioner obtained 95% “Very Eligible”. Trial product carried out in two stages that is scale small and scale big . Questionnaire response student scale test small 94% “Very Interesting ”. Questionnaire response student scale big 96% “ Very Interesting ”, and the questionnaire teacher response scale large 96% “ Very Interesting . The use of Domica media is stated effective after the N-Gain test. The mean value test result is 61.39 or > 56. So it can be concluded effective use of Domica learning media For increase ability numeracy student grade 4 school base